PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN QUIZIZZ UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII SMP SANTO YOSEPH PADA MATERI BANGUN RUANG - Emininta Br Ginting; Imelda Sihombing; Ribka Kariani Sembiring; Friska Ledina Situngkir; Sondang Noverica (STKIP Subang, 2025)
This study aims to determine whether the application of the discovery learning model assisted by quizizz can improve the mathematical understanding of class VII students of SMP Santo Yoseph and to determine how the application of the discovery learning model assisted by quizizz improves the mathematical understanding of class VII students of SMP Santo Yoseph. This research method uses Classroom Action Research (CAR). The research procedure is in the form of a cycle. Each cycle consists of 4 stages, namely: planning, implementing actions, observing, and reflecting. Data collection techniques through observation and testing. This data collection uses several instruments in the form of teacher activity observation sheets and student activity observation sheets, while tests are used to determine students' mathematical understanding abilities. The results of the study indicate that the use of the discovery learning model assisted by quizizz can improve students' mathematical understanding abilities in mathematics lessons on spatial geometry material. From the average value of initial ability, which is 52.73 (15%), the average value of mathematical understanding ability in cycle I is 63.24 (38%), and the average value of mathematical understanding ability in cycle II is 78.36 (82%), and the average value of teacher and student activity observations in cycle I is 71.5% and 72% and cycle II is 85.5% and 88.5%.